Model and data engineering : 5th International Conference, MEDI 2015, Rhodes, Greece, September 26-28, 2015. Proceedings /: 5th International Conference, MEDI 2015, Rhodes, Greece, September 26-28, 2015. Proceedings. (2015) - Unknown
No abstract available